230k views
1 vote
Simplify 12y^7/18y^-3. Assume y=0

User Chugreevd
by
4.8k points

2 Answers

6 votes

Answer:

its the third one i got that

User Shpongle
by
5.3k points
1 vote

For this case we must simplify the following expression:


\frac {12y ^ 7} {18y ^ {- 3}}

We have that by definition of properties of powers, it is fulfilled that:


a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}

Then, we can rewrite the expression:


12y ^ 7 * 18y ^ 3

By definition of multiplication properties of powers of the same base we have:


a ^ m * a ^ n = a ^ {m + n}

So:


12y ^ 7 * 18y ^ 3 = (12 * 18) * y ^ {7 + 3} = 216y ^ {10}

Answer:


216y ^ {10}

When y = 0 the expression is 0

User Famargar
by
5.3k points